EFEKTIVITAS PENGGUNAAN JENIS MADU TERHADAP MASKULINISASI IKAN GUPPY (Poecilia reticulata) MELALUI TEKNIK PERENDAMAN INDUK BUNTING - Nunik Cokrowati; Nurmaya Safitri; Andre Rachmat Scabra (Universitas Sriwijaya, 2022)
Sex reversal or gender inflection is a technique aimed at causing the male development of the female sex (masculinization) and masculine gender to females. One of the most often employed intricate sex techniques is masculinity. Generally, the production of single male sex cells involves taking advantage of the hormone steroid as well as natural substances. The purpose of the study is to know the effectiveness of a different kind of honey in the inbreeding of a guppy mother stem stem (Poecilia reticulata) with the percentage of male fish. The study was carried out in fish reproductive laboratories, the department of agriculture, the university of Mataram in April-Juni 2022. The study employed experimental methods of a complete random model (ral) with 4 treatments, namely P0 (control), P1 (forest honey), P2 (cattle honey), and P3 (mangrove honey). Treatment is repeated three times each. An analysis of the gender percentage carried with analysis of variance (anova) and Duncan's test. The take notes that the percentage of the male fish in forest honey, cattle honey, and mangrove honey are produced in successive percentage of the male fish at 84%, 83%, and 95%. The results of a 100% survival rate rate on all treatment, the absolute heavy growth shows the same conservative value of.38-0.39g, and the specific growth of weight indicates a value of 2.86-2.87%. It can thus be deduced that treatment with the use of mangrove honey is the treatment of the highest effectiveness in the direction of the guppy (Poecilia reticulata) fish.